LEGAL PROTECTION FOR CONSUMERS IN CONDUCTING ELECTRONIC TRANSACTIONS - Imelda Mardayanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Electronic transactions are legal actions carried out using computers, computer networks, and/or other electronic media. Violations of consumer rights, especially in electronic transactions, need to be addressed through statutory regulations. The purpose of this research is for consumers in conducting electronic transactions to know legal remedies that can be taken to find out the form of legal protection for consumers in conducting electronic transactions in Indonesia. The research method is normative law because it examines legal principles, legal systematics, and the level of legal synchronization.Legal remedies that can be taken by consumers when they get goods that are not in accordance with what is offered by the seller, namely through the court and outside the court, as well as legal protection for consumers in conducting electronic transactions are contained in Law Number 8 of 1999 concerning Consumer Protection and in Law Number 11 of 2008 concerning Information and Electronic Transactions.